Model knowledge sharing pada grup Facebook Backpacker Dunia - Galih, Aulia Puspaning (Jurnal Kajian Informasi dan Perpustakaan, 2018)
Facebook is the largest networking site in the world with a growing number of users. Currently, Facebook has evolved into a site that can be used for information sharing by individuals through their personal accounts in the group called âBackpacker Duniaâ, totaling 104,130 members whose hobby is traveling all over the world. This study aimed to identify (1) the relationship between commitment, excitement of helping others, reputation, and the groups appreciation of attitudes towards knowledge sharing, (2) the relationship between attitudes toward knowledge sharing and purpose of knowledge sharing, (3) the appropriate model for knowledge sharing in this study. This knowledge sharing model was adapted from the Theory of Reasoned Action (TRA). The method used in this study was quantitative with an online questionnaire instrument to facilitate the collection of data because the respondents were in cyberspace. SEM-PLS and Smart-PLS 3.0 were used as methods and tools for data analysis and constructing a knowledge sharing model in this study. The number of respondents in the study was 54 people. In the model proposed in the study were 4 hypotheses in the tested coefficient path and one of them was not significant. The study reveals that the relationship between commitment and attitude toward knowledge sharing is not significant, while the relationship between excitement of helping others and attitude towards knowledge sharing; reputation and attitude towards knowledge sharing; attitude toward knowledge sharing and purpose of knowledge sharing are significant.